Impact of Visual Kinesthetic Illusions on Reciprocal Inhibition and Motor Function - Takeru Okouchi; Ryo Hirabayashi; Nao Sugai; Hirotake Yokota; Chie Sekine; Tomonobu Ishigaki; Makoto Komiya; Kodai Sakamoto; Mutsuaki Edama (Applied Sciences)
Reciprocal inhibition is often diminished in elderly individuals and those with upper motor neuron disorders. This reduction in reciprocal inhibition can hinder smooth joint movement. For subjects who have increased muscle tone and a limited range of motion in the joints, we focused on visual kinesthetic illusions as an intervention to increase reciprocal inhibition. We aimed to investigate the effects of visual kinesthetic illusions on reciprocal inhibition and motor function in the ankle joint. Participants participated in two experiments measuring reciprocal inhibition, namely reciprocal Ia inhibition and D1 inhibition, as well as motor functions related to ankle dorsiflexion and plantar flexion. Visual kinesthetic illusion was induced by displaying an image of each subject’s foot on a monitor. Our results showed that the visual kinesthetic illusion enhanced D1 inhibition and improved motor function in the ankle joint by prioritizing agonist muscle activity. We also observed a correlation between reciprocal inhibition and the muscle activity ratio. These findings suggest that visual kinesthetic illusions may improve motor function by increasing reciprocal inhibition. This study is the first to demonstrate the effects of visual kinesthetic illusion on reciprocal inhibition, and we believe that these findings can be applied in rehabilitation.